Australia w literaturze polskiej - Bąk, Magdalena (Postscriptum Polonistyczne, 2020)
Australia has never became a popular topic in Polish literature. However, it was present in Polish writings since the Age of Enlightenment. The aim of the text is to analyse different ways in which Australian motifs were used in different literary works.